The cluster panacea? An evaluation of three interventions in shrimp value chains in Bangladesh - Narayanan, Sudha; Belton, Ben; Kabir, Razin; Sakil, Abdul Zabbar; Khan, Asraul Hoque; Hernandez, Ricardo (International Food Policy Research Institute, 2024)
Clustering farming has often been proposed as an effective way to overcome the significant transactions costs faced by downstream buyers in interacting and negotiating with many small farmers, while making it easier for extension workers and governments to dispense advice, provide upstream services and inputs. In this study, we evaluate the impact of a set of three initiatives in Bangladesh, implemented by a government department, a private sector processing firm and a not-for-profit industrial advocacy body, all involving clustering contiguous shrimp farm ponds to enable group certification necessary for global market access. We implement a canonical difference-in-differences model using two rounds of surveys of a sample of over 1,222 farmers in 2023 and 2024 to assess the impacts on pond management practices, net profits and any unintended impacts on food security and dietary diversity. Our results suggest that the cluster interventions had impressive impacts on adoption of better farm management practices. However, these do not appear to translate into significant gains in net profits, perhaps because these interventions are still relatively new. Further, it appears that cluster farmers pay a penalty on account of a shift to more intensive cultivation, represented by a loss in species diversity and lower incomes from fish and vegetables. We find that there are no significant spillover effects as yet on shrimp farmers in the same village as the clusters. This study reflects critically on the efficacy of clustering that is presumed to enhance access to global markets.